Design And Development Of A Virtual Frequency Meter - Rosli, Zamry (Universiti Sains Malaysia, 2006)
Recently in the radio amateur's practice became popular the so-called virtual measuring meters. In this case by "virtuality" is implied the fact that a certain part of the functions or its main measuring meter realizes with the aid of the personal computer. Virtual measuring meters can be conditionally broken into two categories. The instruments of the first group "are completely virtual" and actually they consist of one program for computer, and functions on the input-output of the measured or generatable signal are placed on the regular hardware. The instruments of the second group have besides "virtual" part even and material. With a 4MHz maximum frequency, a selectable time base of 0.1 seconds, 1.0 second, 10 seconds and 100 seconds, the hardware can measure frequency of digital signal up to the 4MHz crystal limit. A comparator is needed to measure analog signal. To the computer in this case the certain device, which is the main part of the virtual instrument, is connected. Such devices realize some functions or knots of measuring meter. These devices can have different complexity - from "heaped" industrially produced interface boards, built in into the computer, to the simple devices, connected to the computer through computer serial port.